Relationships between media exposure and knowledge, attitude, and practice on HIV/AIDS: a cross sectional survey of adolescent Islamiyya girls in Nigeria - Muhammad Hamid, Adamu; Tamam, Ezhar; Osman, Mohd Nizam (Routledge, 2020)
Exposure to HIV/AIDS media among adolescents in sub-Saharan Africa was reported as low in the early 2000s, but now given developments in technology and program appeal, there emerges a need for reassessment. Given that communication, particularly through the media plays a major role in stemming the spread of the epidemic, this study examines the HIV/AIDS media exposure, knowledge, attitude, and practice (KAP) of adolescent Islamiyya girls in northern Nigeria as a predominantly Muslim society. The objectives of the study were to (1) identify the girls' major sources of information on HIV/AIDS; (2) assess their exposure to HIV/AIDS media and their HIV/AIDS knowledge, attitude and practice; and (3) verify relationships between media exposure and HIV/AIDS KAP. Based on the Advertising Research Foundation's Hierarchy of Effects model, hypotheses were posed to test the relationships. A questionnaire survey was administered on a randomly selected sample of 500 Islamiyya girls in Bauchi, Nigeria, from an estimated population of 35,000. Results were analyzed using descriptive statistics and partial least squares structural equation modeling. The results showed media exposure is not a significant predictor of HIV/AIDS practice, but it is a significant predictor of HIV/AIDS knowledge. And HIV/AIDS knowledge significantly predicted both HIV/AIDS attitude and practice. HIV/AIDS attitude also significantly predicted HIV/AIDS practice. It is thus concluded that among Nigerian adolescent girls, exposure to HIV/AIDS media is a necessary but not a sufficient predictor of HIV/AIDS KAP.